ANALISIS AKUNTABILITAS KEUANGAN DAN PENDAYAGUNAAN DANA ZIS (STUDI KASUS PADA LAZ EL-ZAWA) - Muhammad Iqbal Tawakkal (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analyze the application of financial accountability and utilization of El-Zawa’s ZIS funds. This research is a descriptive qualitative using a case study approach and primary data. To motivate muzakki to pay ZIS through OPZ, the credibility of OPZ should be improved by applying accountability values which are trustworthy, professionalism, and transparency. The results show that the eL-Zawa is untrustworthy in utilizing ZIS because most zakat funds are not channeled to mustahik. The application of accounting of eL-Zawa still has some differences with SFAS 109 and not produced comprehensive financial reports, as there is no note of financial reports (CALK). The professionalism is demonstrated by providing services and ease to deposit ZIS funds for muzakki through the cashier of eL-Zawa in the office, charity tube (tabung amal), and bank account. However, the professionalism of eL-Zawa is still hampered, as some employees have multi-positions in the organization, so the internal controls are assumed to be weak. EL-Zawa transparency values are implemented by publishing program and financial reports through website and a magazine once in a year. In addition, eL-Zawa also provides transaction and deposit proofs to muzakki who deposit ZIS funds. Keywords: credibility, accountability values, ZIS utilization